2002
DOI: 10.1002/1099-0690(200207)2002:14<2257::aid-ejoc2257>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of a Racemic Allyl β-Keto Ester Catalyzed by Nickel Complexes: Asymmetric Induction

Abstract: The nickel-catalyzed electroreductive cleavage of the allyl group of allyl 2-methyl-1-tetralone-2-carboxylate and allyl transfer to the carbonyl group has been examined. The control of the reaction conditions allowed us to orientate the se-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…Deprotection of allyl carbonates using this system has also been described. 662 Hudlicky and co-workers found that cinnamyl group exhibited lower reduction potentials (absolute value) compared to simple allyl groups. Cinnamyl ethers could, therefore, be reduced without a nickel mediator.…”
Section: Cathodic Reductionmentioning
confidence: 99%
“…Deprotection of allyl carbonates using this system has also been described. 662 Hudlicky and co-workers found that cinnamyl group exhibited lower reduction potentials (absolute value) compared to simple allyl groups. Cinnamyl ethers could, therefore, be reduced without a nickel mediator.…”
Section: Cathodic Reductionmentioning
confidence: 99%
“…Constant current electrolysis of 89 in a single compartment cell using a sacrificial Mg anode was conducted in the presence of a Ni catalyst and chiral ligand 90 . After esterification and purification, 91 was isolated in a good yield and with moderate enantioselectivity [70].…”
Section: Reviewmentioning
confidence: 99%
“…Electrocatalytic reductions have also been carried out using metal catalysts, including a Rh III polypyridyl complex for the hydrogenation of acetophenone with modest chiral induction [98]. Other early electroreductive metal-catalyzed enantioselective processes include cobalt catalysis in the form of vitamin B 12 [99][100][101] , as well as nickel catalysis [102] for dehalogenations, isomerizations, reductive cleavages, etc.…”
Section: Reductive Transformationsmentioning
confidence: 99%